PENGARUH SUPLEMENTASI PROBIOTIK YANG BERBEDA PADA AIR MINUM TERHADAP SEL DARAH MERAH(SDM) DAN NILAI PACKED CELL VOLUME(PCV) AYAM BROILER - Alghazali, Fiqri; Suharyati, Sri; Santosa, Purnama Edy (Jurnal Riset dan Inovasi Peternakan, 2018)
This research intended to determine the level of broiler chickensred blood cell(RBC) and Packed Cell Volume (PCV) which is supplementedwith various types of probiotics in drinking water.  This research was conducted in January--February 2018 at Pesawaran Farm.  The RBCand PCV analysis was done in Balai Veteriner Lampung.  The research used Completely Randomized Design with 4 treatments and 3 replications.  The treatment is used P0 (without probiotics supplementation), P1 (supplemented with probiotic A), P2 (supplemented with probiotic B), and P3 (supplemented with probiotic C).  The results showed that probioticssupplementation was significant (P>0,05) on broiler RBC and PCV.  The broiler chickensRBC and PCVanalysis show the P1 treatment (supplemented with probiotic A) have higher on RBC and PCV value compared P0 (without probiotics supplementation), P2 (supplemented with probiotic B), and P3 (supplemented with probiotic C). Key words: Broiler chickens, Packed cell volume,Probiotic, Red blood cell